Evaluasi Sistem Drainase Di Wilayah Kampus Universitas Islam Negeri Sultan Syarif Kasim, Riau - Wendi Nofriandi; Bambang Sujatmoko; Andy Hendri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
A University should have an integrated drainage system so that when it rained, there is no a flood that disrupts the activity of students and teachers on campus. Floods with a height of 5 to 10 cm that ever happened on the campus of UIN SUSKA Riau is the problem of existing drainage systems on the campus of UIN. The drainage that was built in 2016 are expected to resolve the problem of flooding. This study aims to evaluate the drainage system of the UIN SUSKA’s campus use return periode of 2, 5 and 10 years. The data that are used in this research are rainfall’s data, drainage network map, topographic maps and maps of land use. HEC-RAS 4.0 program was used to building model the flow of discharge into the drainage channels of  UIN’s campus. The results showed that the existing drainage is not able to withstand the flood discharge on  return periode 2, 5 and 10 years with a high range of pools is 8 to 11 cm. Then, the evaluation that is done on a planned drainage to be indicating that the planned drainage capable of accommodating the flood discharge with return periode 2, 5 and 10 years.This indicates that the integrated drainage system on a campus, capable of resolving the problem of flooding in the area  Keyword : floods, drainage, HEC-RAS 4.0